ANALISIS DAN PERANCANGAN APLIKASI PEMESANAN TIKET BUS BERBASIS ANDROID - Alwi Marta Suzana (Universitas Teknokrat Indonesia, 2021)
PO Puspa Jaya is a company that is growing rapidly and is a company that is taken into account in land transportation services in Lampung. but in its service puspa jaya still perform manually, such as ticket booking, departure schedule information, and payment transactions carried out at pull puspa jaya. For that, there is a need for supporting facilities to book tickets at pull puspa jaya. From this problem came the idea to create an android-based application, which can make bus ticket reservations in po puspa jaya. The method used in the creation of applications is the Waterfall method. Programming language used by Android studio. With a MySQL support database. The testing method used is ISO 9126 (Usability, Fungtionality, Portability, Efficiency). Supported by the internet connection in the agency. This application will later be used as a medium of ticket booking and passenger data control. This application is for several features, namely determining the time and destination of departure, choosing the desired seat, tray information, contact information and information about. The ticket booking application in po puspa jaya has been tested using ISO 9126 which consists of four aspects of testing namely Usability, Fungtionality, Portability, Efficiency. The Usability aspect obtained an 80.50% result with a decent record. Fungtionality gets 100% results